Avaliação de diferentes fontes de nitrogênio e concentração de sacarose na produção de ácido cítrico por Aspergillus niger usando manipueira como substrato - Pastore, Neivair Sponchiado (2010)
It is necessary to use substrates of low cost and wide availability to the industrial production of citric acid. In this way, manipueira a liquid waste from the cassava industrialization possesses characteristics that make use of great interest as a substrate. This work aimed to the production of citric acid by submerged fermentation using cassava wastewater as substrate and supplemented with sucrose by the fungus Aspergillus niger and different sources of nitrogen such as ammonium sulphate, urea and peptone. The fermentation was conducted in Erlenmeyer flasks and bacteriological incubator. Apart from cassava, for comparative purposes of production of citric acid was used the synthetic medium of Prescott & Dunn. Through the results, we found the production of citric acid fermentation in all media tested. The use of peptone associated with the use of ammonium sulfate to the synthetic medium Prescott & Dunn, had a better production (62.9 g/L citric acid) under the conditions studied. For a medium containing cassava the interaction between urea and ammonium sulfate, showed higher yield (78.4 g/L). Regarding the time for fermentation, it was found that the time of 24 h is ideal for higher productivity in the process. By analyzing the concentration of cyanide and COD of the fermentation medium it was obtained a significant reduction in both factors, the pollutant load of cassava was reduced by 53% compared to the initial value of COD content and the initial 0.4 mg/L cyanide decreased to 0.09 mg/L. It was concluded that the feasibility of using cassava to obtain citric acid under the development of clean technologies, converting the residue in a product with higher added value.